Pengolahan Limbah Pewarna Metilen Biru Menggunakan Arang Aktif dan Zeolit Aktif dengan Katalis Fe dan Oksidator Hidrogen Peroksida - Maryudi Maryudi; Agus Aktawan; Shinta Amelia (Jurnal Riset Kimia, 2021)
The textile industry including batik has provided broad benefits to society from an economic standpoint. However, there is negative impact from wastewater generated in the production process, which is containing dyes. Various types of dyes are used in the coloring process, and methylene blue is one of most used dye. Various ways have been done to treat wastewater containing methylene blue. Methylene blue processing techniques by adsorption have been carried out with various types of adsorbents. Research on the comparison of the ability of commercial activated charcoal and commercial activated zeolite to adsorb methylene blue was carried out with the addition of an Fe catalyst and a hydrogen peroxide oxidizer. The results showed that the addition of Fe catalyst would increase the degradation of methylene blue in the waste either with activated charcoal or activated zeolite. The combination of using Fe catalyst and hydrogen peroxide oxidizer further increases the removal of methylene blue in both types of adsorbents, activated charcoal and activated zeolite. Activated zeolite has the better ability to adsorb methylene blue than activated charcoal under various conditions.